2013
DOI: 10.14233/ajchem.2013.oh91
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Development on Coal Waste Pile in Panyi Coal Mine

Abstract: Exploitation and utilization of coal can result in a series of ecological environment problems. Coal waste was the solid waste released in the process of coal mining. When coal waste was dumped to form pile, it not only occupies lots of arable land, but also endangers the ecological system in coal mine district. In this study, coal waste pile of Panyi coal mine were surveyed for naturally occurring plant species and limiting factors for plant residence. The plant species, Summed dominance ratio, Species divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The addition of fly ash can improve the water-holding capacity and permeability of coal gangue (Wang et al, 2017; Zheng et al, 2022). Wang and Cai (2008) revealed that adding substrate amendments such as fly ash to coal gangue piles can motivate plant growth. The coal gangue and fly ash have been explored in a reasonable proportion as a material for soil reconstruction in mining areas (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fly ash can improve the water-holding capacity and permeability of coal gangue (Wang et al, 2017; Zheng et al, 2022). Wang and Cai (2008) revealed that adding substrate amendments such as fly ash to coal gangue piles can motivate plant growth. The coal gangue and fly ash have been explored in a reasonable proportion as a material for soil reconstruction in mining areas (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%